History of greed : financial fraud from tulip mania to Bernie Madoff - Sarna, David E. Y. (Wiley, 2010)
The inside stories of some of the more infamous names associated with financial fraud, along with commentary about why we ignore the lessons of the past and fall prey to the promise of easy money